Canopy Structure, Light Intensity, Temperature and Photosynthetic Performance of Winter Wheat under Different Irrigation Conditions - Meng Zhang; Weiwei Chen; Maoya Jing; Yanmei Gao; Zhimin Wang (Plants, 2023)
A high-quality canopy architecture is central to obtaining high crop yields. A field experiment was carried out at the Wuqiao Experimental Station from 2015 to 2019 under four irrigation schemes (W0, no irrigation after sowing; W1, 75 mm irrigation at jointing stage; W2, 75 mm irrigation at jointing and anthesis stages, respectively; W3, 75 mm irrigation at tillering, jointing and anthesis stages, respectively) to investigate the canopy structure, canopy apparent photosynthesis (CAP), canopy temperature (CT), yield and water use efficiency (WUE). The results showed that increasing irrigation times improved the leaf area index (LAI), non-leaf area index (NLAI) and light interception (LI) of the spike and total canopy but decreased the canopy temperature (CT) after anthesis. The CAP in the W3 treatment was consistently lower than that in the W1 treatment, suggesting lower effective utilization of light energy under the W3 treatment. Increasing irrigation times improved wheat yield, but the W2 treatment had no significant difference in yield compared to the W3 treatment. In addition, the W1 and W2 treatments had higher WUEs. The CT, organ temperature and LI were closely positively associated with each other, but they were all strongly negatively related to the yield. Overall, the W2 treatment was the best irrigation scheme for constructing a reasonable canopy architecture for winter wheat, obtaining more efficient water use and yield in the North China Plain (NCP). CT and organ temperature can be used as proxy parameters to estimate the canopy structure.